2014
DOI: 10.1039/c4cp02078b
|View full text |Cite
|
Sign up to set email alerts
|

Tip-enhanced Raman spectroscopic measurement of stress change in the local domain of epitaxial graphene on the carbon face of 4H-SiC(000–1)

Abstract: We develop a bulk silver tip for tip-enhanced Raman scattering (TERS) and obtain TERS spectra of epitaxial graphene on the carbon face of 4H-SiC(000-1) with a high signal-to-noise ratio. Thanks to the high quality of TERS spectra we firstly find that the G band in the TERS spectra exhibits position-by-position variations in both lower wavenumber shifts and spectral broadening. The analysis of the variations reveals that the shifts and broadenings have a linear correlation between each other, indicating that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 34 publications
0
52
0
Order By: Relevance
“…A Raman spectrum in the 4500-1000 cm −1 region at a particular spot in epitaxial graphene on the 4H-SiC (0001) surface measured under tip-retracted conditions is shown in Fig. 9 [40]. Figures 9(a) and (b) depict spectra collected under tip-approaching and tip-retracted conditions.…”
Section: Cmentioning
confidence: 99%
See 4 more Smart Citations
“…A Raman spectrum in the 4500-1000 cm −1 region at a particular spot in epitaxial graphene on the 4H-SiC (0001) surface measured under tip-retracted conditions is shown in Fig. 9 [40]. Figures 9(a) and (b) depict spectra collected under tip-approaching and tip-retracted conditions.…”
Section: Cmentioning
confidence: 99%
“…In the study by Suzuki et al [40] the G band in the TERS spectra of epitaxial graphene on the C-face of 4H-SiC exhibits position-by-position changes in both lower wavenumber shifts and spectral broadening. The analysis of the changes revealed that the shifts and broadenings have a linear correlation between each other, indicating that the changes are induced by the position-dependent local stress on graphene based on a uniaxial strain model.…”
Section: Cmentioning
confidence: 99%
See 3 more Smart Citations